2008
DOI: 10.1162/jocn.2008.20109
|View full text |Cite
|
Sign up to set email alerts
|

Infection, Incest, and Iniquity: Investigating the Neural Correlates of Disgust and Morality

Abstract: Disgust, an emotion related to avoiding harmful substances, has been linked to moral judgments in many behavioral studies. However, the fact that participants report feelings of disgust when thinking about feces and a heinous crime does not necessarily indicate that the same mechanisms mediate these reactions. Humans might instead have separate neural and physiological systems guiding aversive behaviors and judgments across different domains. The present interdisciplinary study used functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(133 citation statements)
references
References 63 publications
(99 reference statements)
12
119
0
Order By: Relevance
“…This is consistent with literature indicating that the insula is preferentially active when people experience disgust (e.g., Chen et al, 2009;Jabbi, Bastiaansen, & Keysers, 2008;Parkinson et al, 2011), particularly so when it is sex-related (e.g., Borg et al, 2008). Moreover, there were no significant within condition differences in insula activation.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with literature indicating that the insula is preferentially active when people experience disgust (e.g., Chen et al, 2009;Jabbi, Bastiaansen, & Keysers, 2008;Parkinson et al, 2011), particularly so when it is sex-related (e.g., Borg et al, 2008). Moreover, there were no significant within condition differences in insula activation.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…The anterior insula (BA 13) is generally involved in the experience of disgust (e.g., Chen et al, 2009;Jabbi et al, 2008;Parkinson et al, 2011). Moreover, some evidence suggests that the insula is particularly sensitive to sex-related disgust (Borg et al, 2008), which is pertinent to our participants' task of viewing and judging newlywed couples. Consistent with this literature, Study 2 participants showed significantly more right insula activation while viewing images of interracial couples relative to same-race couples.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, there are differences in the brain systems that respond to sexual and non-sexual moral norms, as well as to anger and disgust (Moll et al, 2005;Schaich Borg, Lieberman, & Kiehl, 2008). In Schaich Borg et al's (2008) research, pathogen disgust (similar to core disgust) and socio-moral disgust acts were rated as more disgusting than neutral behaviors.…”
Section: Metaphorical Usementioning
confidence: 99%
“…Furthermore, both moral and physical disgust trigger shared features of the classical disgust expression (e.g., Cannon et al, 2011;Chapman et al, 2009). Lastly, evidence from neuro-scientific studies (although not reviewed here since they are outside of the three claims) suggests that both share some overlapping brain networks (e.g., Moll et al, 2005;Parkinson et al, 2011;Schaich Borg, Lieberman, & Kiehl, 2008).…”
Section: Discussionmentioning
confidence: 91%